(untitled) (ModaPalavra e-periódico, 2023)
This article reports the pedagogical experience involved in the application of Cartesian Moulage at the Instituto Federal de Santa Catarina (IFSC), Campus Jaraguá do Sul (Brazil), in particular, in the context of the technical course in Clothing Modeling and the higher technology course in Fashion Design. Methodologically, the article consists of an applied, descriptive and qualitative research. Based on a bibliographic review about the concept of modamática and with the support of a field notebook, the scenario found before and after the application of the technique was narrated. Based on the report, it was inferred that cartesian moulage has potentialities that can be explored by the academic community interested in apparel patternmaking and that, from the students and professors point of view, the technique can contribute significantly to understand the three-dimensionality of the human body when facing the challenge of apparel design.